Housing costs, poverty and inequality in Australia. Issue 6 (18th August 2017) - Saunders, Peter
Abstract: Housing costs have long been recognised as a factor contributing to poverty, and poverty researchers have estimated poverty using income before and after deducting housing costs. This paper examines the treatment of housing in the literatures on poverty and housing and applies the before and after housing costs approach to examine the extent of both poverty and income inequality in Australia and how they have changed since the early 2000s, focusing on the role of housing costs in the periods before and after the global financial crisis (GFC). Account has been taken of changes in the income measure used by the Australian Bureau of Statistics in its household income surveys as these have been shown to have a marked impact on empirical estimates. The findings indicate that taking account of housing costs leads to greater increases in both poverty and inequality between 2003–2004 and 2007–2008 and to smaller reductions in both since the GFC in 2007–2008.